1992
DOI: 10.4319/lo.1992.37.5.0974
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton and episodic suspended sediment loading: Phosphate partitioning and mechanisms for survival

Abstract: Enclosures within a turbid reservoir were used in combination with short-term laboratory experiments to examine some effects of suspended sediment loading on the community structure and phosphate uptake of the phytoplankton. Phytoplankton communities in duplicate field enclosures were treated at 7-d intervals for 8 weeks with a natural, fine-particulate clay in hydrated form, for comparison with species composition and abundances in communities from control enclosures without sediment additions. The phytoplank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 30 publications
2
28
0
1
Order By: Relevance
“…This suggested that bigger phytoplankton cells (that were not tychopelagic) were less able to cope with sediment loading and were not well adapted to turbid low light conditions. These results correspond to reports that larger phytoplankton cells can be rapidly removed from the water column when exposed to increasing sediment loads (Burkholder 1992).…”
Section: Currents Waves and Turbidly Effects On Microalgal Communitiessupporting
confidence: 73%
“…This suggested that bigger phytoplankton cells (that were not tychopelagic) were less able to cope with sediment loading and were not well adapted to turbid low light conditions. These results correspond to reports that larger phytoplankton cells can be rapidly removed from the water column when exposed to increasing sediment loads (Burkholder 1992).…”
Section: Currents Waves and Turbidly Effects On Microalgal Communitiessupporting
confidence: 73%
“…Particle stabilization, even at the high ionic strength of seawater, may be affected by steric effects due to the presence and adsorption of organic matter in the medium (O'Melia and Tiller, 1993). Burkholder et al (1992) described a related species of Gymnodinium sp. that releases copious amounts of mucous-like organic matter in the presence of high silt and clay.…”
Section: O~~~-~---'----~------r-----------r-----'----~'----------~mentioning
confidence: 99%
“…The larger decrease of SRP concentration inside than outside the plume may be due to phosphate uptake by Stephanodiscus. According to Burkholder (1992), increasing suspended particle concentration enhances phosphate uptake by algae as a survival mechanism under episodic sediment loading. The granulometric data ( Figure 9) and SEM observations corroborate this interpretation: the cell number of the dominant algae, Stephanodiscus, was much higher inside the plume than outside.…”
Section: Biological Factorsmentioning
confidence: 99%
“…Literature conclusions are often conflicting (Burkholder, 1992). A significance of floods in Lake Bourget, mainly on the Phosphorus cycle (P-cycle), has been postulated (Groleau, 1994;Vinçon-Leite et al, 1995).…”
Section: Introductionmentioning
confidence: 99%